Hubungan Kelimpahan Fitoplankton dengan Konsentrasi Klorofil-a di Danau Tanjung Kudu dan Danau Parit Kecamatan Tambang Kabupaten Kampar Provinsi Riau - Hikma, Murbeni; Simarmata, Asmika Harnalin; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Research on the relationship between phytoplankton abundance and chlorophyll-a concentration was conducted in December 2020 in Tanjung Kudu Lake and Parit Lake, Tambang District. The aims of this study was to determine the relationship between phytoplankton abundance and chlorophyll-a concentration. There were 3 Station, namely Station 1 (inlet), Station 2 (middle of the lake), and Station 3 (end of the lake). Sampling point were at the surface and 2 Secchidepth, 4 times once/week. Water quality parameters were measuredsuch as temperature, pH, transparency, depth, DO, free CO2, nitrate, and phosphate. The results shown that the correlation between phytoplankton abundance and chlorophyll-a concentration in Tanjung Kudu Lake andParit Lakerespectively : Y = 1.10+3.19X(r) 0,90 and Y = 0.98+3.77X (r) 0,93. Phytoplankton abundance in Tanjung Kudu Lake range 22,646-50,124 cells/L and in ParitLake range from 25,344-60,985 cells/L. The chlorophyll-a concentration in Tanjung Kudu Lake range from 1.86-2.82 µg/L and in Parit Lake range from 1.86-3.07 µg/L. Water quality parameters such as temperature 29-29.7oC, pH 5.3-5.6, transparency 47.7-57.3 cm, depth 166.7-266.5, DO 3.1-5.1 mg/L, free CO2 9.9-15.9 mg/L, nitrate 0.02-0.04 mg/L, phosphate 0.02-0.04 mg/L in Tanjung Kudu Lake and in Parit Lake : temperature was 29.5-30oC, pH 5.2-5.6, transparency 57.8-67.1 cm, depth 141-240.7, DO 3.7-5.8 mg/L, free CO2 14.9-8.9 mg/L, nitrate 0.02-0.05 mg/L, phosphate 0.02-0.05 mg/L. Based on the data phytoplankton and chlorophyll-a, Tanjung Kudu Lake and Parit Lakecan be categorized as mesotrophic.Keywords: Chlorophyll-a,Mesotrofik, Phytoplankton, oxbow lake, water quality